npj Climate Action - Tosun, Jale.; Bakas, Spyros; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Climate Action considers research that explores all aspects of mitigating the hazardous effects of global climate change. The journal covers a broad range of topics including but not limited to: Mitigation of the effects of climate change Resilience and adaptation Policy and governance Economic impact of climate change Sustainable development practices in business, finance, agriculture, forestry, urban planning, transportation, and waste management Climate justice, equity, and social inclusion Renewable energy technologies Climate engineering, technology, and innovation Community action and grassroots movements Education, outreach, and behavioral studies Coupled human-environment systems The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by climate change experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Environmental sciences$1 (BSocial aspects.s; Environment; Environmental economics; Power resources; Sustainability; Social policy; Environmental Social Sciences; Environmental Sciences; Environmental Economics; Natural Resource and Energy Economics; Sustainability; Social Policy